Assessment of Iodine Status in a Referral-Based Euthyroid Adult Population in Aydın Province: Spot Urinary Iodine Concentration, Iodine/Creatinine Ratio, and Serum Thyroglobulin Levels - Ayça Tuzcu; Kenan Yörük; Gülnur Taşçı Bozbaş; Aslıhan Büyüköztürk; Mustafa Yılmaz (Journal of Turkish Clinical Biochemistry, 2026)
Objective: To assess iodine status in adults with euthyroid in Aydın province using spot urinary iodine concentration (UIC) and the urinary iodine-to-creatinine (I/Cr) ratio and to evaluate the relationship between serum thyroglobulin (Tg) and iodine status. Methods: This retrospective study included 162 euthyroid and anti-Tg-antibody-negative adults evaluated between 2023 and 2025, with simultaneous spot UIC, urinary creatinine, and serum Tg measurements. Participants were classified per World Health Organization (WHO) criteria as iodine-deficient (UIC